Ursodeoxycholic acid protects against lung injury induced by fat embolism syndrome. Issue 24 (4th November 2020) - Niu, Fangfang; Li, Huafei; Xu, Xiaotao; Sun, Lingling; Gan, Ning; Wang, Aizhong
Abstract: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a life‐threatening disease with a high mortality rate, which was a common complication of fat embolism syndrome (FES). Ursodeoxycholic acid (UDCA) has been reported to exert potent anti‐inflammatory effects under various conditions. In vivo, perinephric fat was injected via tail vein to establish a rat FES model, the anti‐inflammatory effects of UDCA on FES‐induced lung injury were investigated through histological examination, ELISA, qRT‐PCR, Western blot and immunofluorescence. In vitro, human lung microvascular endothelial cells (HPMECs) were employed to understand the protective effects of UDCA. The extent of ALI/ARDS was evaluated and validated by reduced PaO2 /FiO2 ratios, increased lung wet/dry (W/D) ratios and impaired alveolar‐capillary barrier, up‐regulation of ALI‐related proteins in lung tissues (including myeloperoxidase [MPO], vascular cell adhesion molecule 1 [VCAM‐1], intercellular cell adhesion molecule‐1 [ICAM‐1]), elevated protein concentration and increased proinflammatory cytokines levels (TNF‐α and IL‐1β) in bronchoalveolar lavage fluid (BALF). Pre‐treatment with UDCA remarkably alleviated these pathologic and biochemical changes of FES‐induced ALI/ARDS; our data demonstrated that pre‐treatment with UDCA attenuated the pathologic and biochemical changes of FES‐induced ARDS, which provided a possible preventive therapy for lung injury caused by FES.